2014
DOI: 10.1371/journal.pone.0111368
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Mechanical Properties of Third-Generation Artificial Turf Systems on Soccer Players’ Physiological and Physical Performance and Their Perceptions

Abstract: The aim of this research was to evaluate the influence of the mechanical properties of artificial turf systems on soccer players’ performance. A battery of perceptive physiological and physical tests were developed on four different structural systems of artificial turf (System 1: Compacted gravel sub-base without elastic layer; System 2: Compacted gravel sub-base with elastic layer; System 3: Asphalt sub-base without elastic layer; System 4: Asphalt sub-base with elastic layer). The sample was composed of 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 60 publications
(86 reference statements)
5
62
0
Order By: Relevance
“…Potentially a higher energy restitution association with a greater firmness of a surface may have caused a higher workload on the softer grass (Kerdok et al, 2002;Katkat et al, 2009). A lower impact peak on softer grass may be attributable to the inability to produce force rapidly (McGhie and Ettema., 2013) which may have altered joint movement patterns (Hamill et al, 1992), influencing the vertical deformation (Sánchez-Sánchez et al, 2014) and increasing the eccentric muscle activity (Richie et al, 1993). There were also greater frequencies of low and high intensity periods on the softer surfaces meaning high intensity activity was more intermittent on softer surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially a higher energy restitution association with a greater firmness of a surface may have caused a higher workload on the softer grass (Kerdok et al, 2002;Katkat et al, 2009). A lower impact peak on softer grass may be attributable to the inability to produce force rapidly (McGhie and Ettema., 2013) which may have altered joint movement patterns (Hamill et al, 1992), influencing the vertical deformation (Sánchez-Sánchez et al, 2014) and increasing the eccentric muscle activity (Richie et al, 1993). There were also greater frequencies of low and high intensity periods on the softer surfaces meaning high intensity activity was more intermittent on softer surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These systems are characterized by long fibers in the carpet (40-65 mm), a relatively low tuft density, and, most of all, the presence of large quantities of infill in comparison to first or second generation products, with usually a sand layer at the base and crumbed rubber at the top [7]. Also, a shockpad layer is often placed underneath the grass carpet [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified the condition of the playing surface as a parameter that affects football players' safety and performance [2,9,10]. Therefore, to promote football in a responsible way and to safeguard the safety and the integrity of the performance of all athletes, it should be permanently guaranteed that these surfaces comply with appropriate quality standards [8]. To do so, any artificial turf football pitch, new or used, should be submitted periodically to maintenance tasks and evaluation tests to ensure that its surface has been installed correctly and meets those quality standards.…”
Section: Introductionmentioning
confidence: 99%
“…As each situation is unique, a successful player has the ability to adapt and perform the technical moves that are most appropriate with regard to the playing surface. Previous studies suggest different perceptions between the systems of artificial turf, which generate differences in the physical performance and in the soccer players' performances [4]. Soccer has traditionally been played on grass, which has certain requirements as it is a living plant that changes with the seasons [5].…”
Section: Introductionmentioning
confidence: 99%